Gambaran Distres Psikologis pada Petani Tembakau Di Kecamatan Kalisat Kabupaten Jember - Alviolita Nur Septiani; Emi Wuri Wuryaningsih; Enggal Hadi Kurniyawan (Pustaka Kesehatan, 2019)
Serious problems experienced by tobacco farmers are narrowing land area, decreasing land fertility, degradation of agricultural land, pest attacks, inappropriate fertilization to tobacco plants, weather and crop failure. Those problems posed the tobacco farmers at risk of psychological distress. This study aimed to analyze psychological distress in tobacco farmers in Kalisat, Jember. The design of this study was descriptive analysis with cluster sampling and proportional sampling techniques. The population of this study was tobacco farmers, as many as 91 (CI = 90%). The research instruments were the 42 Depression Anxiety and Stress Scale questionnaires (DASS 42) (Cronbach's Alpha 0.776; 0.931; 0.803). The results showed that tobacco farmers had the highest anxiety (73.6%), stress (26.4%), and depression (11%). Psychological distress in farmers is manifested in the form of worries and fears of work which is generally due to instability from the work of farmers.